Cardiac Structural and Functional Changes in Acute Myocardial Infarction - L. I. Sergeyeva; V. L. Kozhura; Yu. A. Churlyaev (Общая реаниматология)
Twelve patients with acute myocardial infarction and 41 patients with postinfarct cardiosclerosis complicated by NYHA Functional Classes I—IV chronic heart failure (CHF) were examined. The structural and functional status of the left and right cardiac cavities was evaluated by echocardiography. Remodeling processes separately occurred in the left ventricle (LV) in the acute period of myocardial infarction. The structural and functional rearrangement of the right cardiac chambers in patients with CHD and CHF proceeds simultaneously with LV remodeling processes, starting from the earliest stages. In patients with CHF and rigid diastolic dysfunction with normal LV filling pressure and mean pulmonary and right atrial pressures, the observing dilatation of the right ventricle is one of the signs of its remodeling.